"Minne" and the Grail in Wolfram's "Parzival" - Greenfield, John (2014)
This article discusses the role of worldly minne within the spiritual domain of the Grail. Certain members of the Grail family (Anfortas, Trevrizent, Sigune and Herzeloyde) seem particularly open to problems concerning courtly love; within Grail society secular minne cannot be the highest ideal, but merely a stage on the way to full consummation of Gottesminne.